Which one? A comparative study of traditional and sports uniforms on academic achievement, cognitive performance, playtime, bullying, and discrimination in adolescents: The Cogni-Action Project - Cristi-Montero, Carlos; Solis-Urra, Patricio; Sanchez-Martinez, Javier; Olivares-Arancibia, Jorge; Hernández-Jaña, Sam; Gajardo-Araya, Guillermo; Palma-Leal, Ximena; Sadarangani, Kabir P.; Portela Estinto, Matias; Encina, Yonatan; Alvarez, Cristian; Delgado-Floody, Pedro; et al. (Frontiers in Public Health, 2022)
Objective The aim of this study was to compare academic achievement, cognitive performance, playtime, bullying, and discrimination in adolescents according to traditional uniforms (TUs) and sports uniforms (SUs) worn at school, while simultaneously exploring the influence of the school vulnerability index. Methods A total of 988 Chilean adolescents (52.6% boys) aged 10–14 years participated in this cross-sectional study. Academic achievement was evaluated by the average grade in maths, language, and science grades, while cognitive performance was assessed through eight cognitive tasks. TUs affecting physical activity, playtime, bullying, and discrimination were queried. Mixed model analyses were performed. Results No differences were observed in academic achievement (TU: 5.4 ± 0.1 vs. SU: 5.5 ± 0.2, p = 0.785) or in cognitive performance (TU: 99.6 ± 0.8 vs. SU: 98.9 ± 1.8, p= 0.754) according to the school uniformtype. Moreover, 64.1 % of participants declared that wearing TU affects their physical activity (traditional uniforms: + 8 min and sports uniforms: + 20 min), and those who believed so spent more time playing than those who answered negatively (14.5 min, p = 0.012). Finally, adolescents wearing SU displayed a lower feeling of bullying and discrimination; this finding depended mainly on the school's vulnerability. Conclusion It is concluded that wearing TU does not show an educational advantage at an academic and cognitive level that justifies its obligation. In addition, it could be suggested that schools consider adolescents' opinions in adopting a more comfortable uniform, such as the SU. This feasible and low-cost measure would help to increase adolescents' physical activity during the school day, and, contrary to belief, it would not be related to increased feelings of bullying and discrimination.